Geological Characteristics and Distribution of Granite Geothermal Reservoir in Southeast Coastal Areas in China - Zheng, Herong; Luo, Jun; Zhang, Ying; Feng, Jianyun; Zeng, Yan; Wang, Mingchuan (Frontiers in Earth Science, 2021)
The southeast coastal areas in China have distributed lots of granite outcrops of different periods. Previous research has shown that granites are also distributed under sedimentary basins in these areas. Therefore, granites with fractures buried in deep can be used as a potential deep geothermal reservoir in these areas. In order to study geological conditions of the deep granite reservoir and establish the genesis model of the deep granite geothermal system, rock geochemistry and zircon U-Pb chronology from outcrop and parts of the drilling cores of granitic rocks have been analyzed, combined with the anatomy of the deep seismic data. Based on the results of geochemistry and zircon U-Pb chronology, most granites in this area are of Yanshanian periods. The formation background of granites is the advance and retraction of westward subduction of Pacific plate. According to the seismic data, the thickness of the overlying strata on granite in Huangshadong area of Huizhou City is up to 1.5 km. According to the regional geological survey, multi-stage joints are developed in the granite, and a large number of hot springs rise to the surface. The heat source in the study area mainly comes from the mantle carried up by the deep NNE-trending faults. There are a large number of thermal springs at the intersection of the surface and the NW-trending fault, and the NW-trending fault provides the drainage conditions for the upwelling of underground thermal springs. There is a huge amount of deep granite geothermal resources in the southeast coastal area. The analysis of deep granite geological conditions and genetic models can provide guidance for the evaluation of deep granite geothermal resources and the further optimization of favorable zones in these areas.